Marianna Napolitano – Federico Ruozzi (eds.): Religious and Identity-based Roots of the War in Ukraine. - Nešpor, Zdeněk R. (Lidé města, 2026)
Recenze knihy Marianna Napolitano – Federico Ruozzi (eds.): Religious and Identity-based Roots of the War in Ukraine.